Entrepreneurship orientation and management ties in the relationship between technological opportunism and innovation performance - Yanuar Nugroho; Noorlailie Soewarno (Cogent Business & Management, 2024)
During economic crises, innovation performance becomes a critical driver of competitiveness. Technological opportunism is recognized within dynamic markets as a key driver for innovation development. However, gaps persist in understanding how technological flexibility, pursuit of entrepreneurial opportunities, and resource optimization influence innovation performance. In order to fill these gaps, this study looks at the relationship between technical opportunism and innovation performance while taking managerial ties and entrepreneurial orientation into account as moderating factors. The study, which collected 93 questionnaires from managers, team leaders, branch leaders, and directors of Indonesian banks, finds a favourable and statistically significant correlation between technological opportunism and innovation performance. It was discovered that managerial ties and entrepreneurial inclination moderated this link. The findings contribute to bridging knowledge gaps in entrepreneurship, technology, and innovation, particularly within the banking industry.
Keywords: 650; Entrepreneurship; innovation performance; managerial ties; technological opportunism; economy